Bio-products from algae-based biorefinery on wastewater: A review. (1st September 2021) - Catone, C.M.; Ripa, M.; Geremia, E.; Ulgiati, S.
Abstract: Increasing resource demand, predicted fossil resources shortage in the near future, and environmental concerns due to the production of greenhouse gas carbon dioxide have motivated the search for alternative 'circular' pathways. Among many options, microalgae have been recently 'revised' as one of the most promising due to their high growth rate (with low land use and without competing with food crops), high tolerance to nutrients and salts stresses and their variability in biochemical composition, in so allowing the supply of a plethora of possible bio-based products such as animal feeds, chemicals and biofuels. The recent raising popularity of Circular Bio-Economy (CBE) further prompted investment in microalgae, especially in combination with wastewater treatment, under the twofold aim of allowing the production of a wide range of bio-based products while bioremediating wastewater. With the aim of discussing the potential bio-products that may be gained from microalgae grown on urban wastewater, this paper presents an overview on microalgae production with particular emphasis on the main microalgae species suitable for growth on wastewater and the obtainable bio-based products from them. By selecting and reviewing 76 articles published in Scopus between 1992 and 2020, a number of interesting aspects, including the selection of algal species suitable for growing on urban wastewater, wastewater pretreatment and algal-bacterial cooperation, were carefully reviewed and discussed in this work. In this review, particular emphasis is placed on understanding of the main mechanisms driving formation of microalgal products (such as biofuels, biogas, etc.) and how they are affected by different environmental factors in selected species. Lastly, the quantitative information gathered from the articles were used to estimate the potential benefits gained from microalgae grown on urban wastewater in Campania Region, a region sometimes criticized for poor wastewater management. Graphical abstract: Image 1 Highlights: Microalgae grown on wastewater is a promising circular pathway. Depending on the microalgae species, several bio-based products can be gained. This review maps the products obtainable from algae and their possible applications. Potential economic and environmental benefits at global and local level are discussed.